(untitled) (International Journal of Engineering and Computer Science, 2015)
A Social network is a Social structure made up of a set of social actors (such as individuals or organizations) and a set of dyadic ties between these actors. Like their public counterpart such as Face book and twitter, enterprise social network are poised to revolutionize how people interact in the work place. Enterprise social networking focuses on the use of online social network or social relations among people who share business interests and/or activities. Collaboration is so common in today’s society. It is proven powerful for solving problems, building consensus, and helping decision making processes. An activity log is written record of how you spend your time. Activity log will also help you understand whether or not you are doing your most important work during the right time of your day.